CAR Triggered Release of Type-1 Interferon Limits CAR T-Cell Activities by an Artificial Negative Autocrine Loop - Harrer, Dennis Christoph; Schenkel, Charlotte; Bezler, Valerie; Kaljanac, Marcell; Hartley, Jordan; Barden, Markus; Pan, Hong; Holzinger, Astrid; Herr, Wolfgang; Abken, Hinrich (Cells, 2022)
The advent of chimeric antigen receptor (CAR) T cells expedited the field of cancer immunotherapy enabling durable remissions in patients with refractory hematological malignancies. T cells redirected for universal cytokine-mediated killing (TRUCKs), commonly referred to as “fourth generation” CAR T-cells, are designed to release engineered payloads upon CAR-induced T-cell activation. Building on the TRUCK technology, we aimed to generate CAR T-cells with a CAR-inducible artificial, self-limiting autocrine loop. To this end, we engineered CAR T-cells with CAR triggered secretion of type-1 interferons (IFNs). At baseline, IFNα and IFNβ CAR T-cells showed similar capacities in cytotoxicity and cytokine secretion compared to conventional CAR T-cells. However, under “stress” conditions of repetitive rounds of antigen stimulation using BxPC-3 pancreas carcinoma cells as targets, anti-tumor activity faded in later rounds while being fully active in destructing carcinoma cells during first rounds of stimulation. Mechanistically, the decline in activity was primarily based on type-1 IFN augmented CAR T-cell apoptosis, which was far less the case for CAR T-cells without IFN release. Such autocrine self-limiting loops can be used for applications where transient CAR T-cell activity and persistence upon target recognition is desired to avoid lasting toxicities.
CRIS-Team Scopus Importer:2023-03-23
Keywords: CAR T-cells; inducible; negative feedback; TRUCK